EFFECTIVENESS OF GUIDED QUESTION TECHNIQUE IN ENHANCING THE WRITING ABILITY OF GRADE EIGHT STUDENTS AT SMP NEGERI 1 SIANTAR - Sidauruk, Yanti Elizabeth; Irene Adryani Nababan; Basar Lolo Siahaan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research investigated the effectiveness of the Guided Question Technique in enhancing the writing ability of eighth-grade students at SMP Negeri 1 Siantar during the 2025/2026 academic year. The study employed a quantitative approach using a quasi-experimental design. A total of 62 students were selected as the sample, divided into two groups: class VIII-2 as the experimental group, which was taught using the Guided Question Technique, and class VIII-1 as the control group, which received instruction through the conventional technique. Data collection was conducted by administering pre-tests and post-tests in recount text writing, and the results were analyzed using the t-test formula. The pre-test results revealed that the experimental group obtained an average score of 70.03, while the control group reached an average of 71.16. After the treatment, the post-test results indicated a significant improvement, with the experimental group achieving an average score of 79.90 compared to 74.94 for the control group. The data were gathered using a writing test as the primary research instrument. The t-test analysis generated a t-observed value of 3.551, which was greater than the t-table value of 1.671 at the 5% significance level. These findings demonstrated that the Guided Question Technique significantly improved students’ writing performance. Specifically, it enhanced their ability to organize ideas logically and to construct recount texts in accordance with the generic structure. Therefore, the Guided Question Technique can be regarded as an effective and practical instructional strategy to foster students’ writing competence in junior high school, offering teachers an engaging alternative to conventional technique.